Inhibition of T Cell Receptor Activation by Semi-Synthetic Sesquiterpene Lactone Derivatives and Molecular Modeling of Their Interaction with Glutathione and Tyrosine Kinase ZAP-70; Molecules; Vol. 24, iss. 2 - Khlebnikov A. I. Andrey Ivanovich; Schepetkin (Shchepyotkin) I. A. Igor Aleksandrovich; Kishkentaeva A. S. Anarkul Serikovna; Shaimerdenova Zh. R. Zhanar Rakhimovna; Atazhanova G. A. Gayane Abdulkakhimovna; Adekenov S. M. Sergazy Mynzhasarovich; Kirpotina L. N. Liliya Nikolaevna; Quinn M. T. Mark (2019, 2019)
Title screen